2019
DOI: 10.15666/aeer/1706_1434714357
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Land Tenancy in Rice Farming Efficiency in Upland Karst Mountainous Gunungkidul Indonesia

Abstract: The land area of paddy has decreased every year. Karst as one of the most extensive dry land areas in Indonesia is used to raise paddy as well. This study aims to determine the role of land tenancy in rice farming efficiency and the determining factors of the efficiency of rice farming in the karst mountainous Gunungkidul. The research is located in karst mountainous area of Gunung Sewu, Gunungkidul. This study uses the stochastic frontier analysis with cost function approach. The result shows that the estimat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…It can also be the case that farmers who are more productive, perhaps due to a number of factors, such as capital availability, entrepreneurial spirit and production efficiencies, are the ones that have the financial resources available to rent more land and may therefore already be better placed in terms of raising productivity. A consultation on tenancy reform and call for evidence on farm business repossessions and mortgage restrictions over let land Wales 48 [7] Dynamics and resource use efficiency of agricultural land sales and rental market in India India 49 [32] Arkansas landlord selection of land-leasing contract type and terms US 50 [101] The role of land tenancy in rice farming efficiency Indonesia 51 [102] New entrants and succession into farming Northern Ireland 52 [103] Aging population, farm succession, and farmland usage China 53 [104] The moratorium on agricultural land sale as a limiting factor for rural development International study 54 [105] Effects of land tenure and property rights on agricultural productivity Ethiopia 55 [106] Taxing and untaxing land: Current use assessment of farmland US 56 [107] Land tenure, fixed investment, and farm productivity Zambia…”
Section: Discussionmentioning
confidence: 99%
“…It can also be the case that farmers who are more productive, perhaps due to a number of factors, such as capital availability, entrepreneurial spirit and production efficiencies, are the ones that have the financial resources available to rent more land and may therefore already be better placed in terms of raising productivity. A consultation on tenancy reform and call for evidence on farm business repossessions and mortgage restrictions over let land Wales 48 [7] Dynamics and resource use efficiency of agricultural land sales and rental market in India India 49 [32] Arkansas landlord selection of land-leasing contract type and terms US 50 [101] The role of land tenancy in rice farming efficiency Indonesia 51 [102] New entrants and succession into farming Northern Ireland 52 [103] Aging population, farm succession, and farmland usage China 53 [104] The moratorium on agricultural land sale as a limiting factor for rural development International study 54 [105] Effects of land tenure and property rights on agricultural productivity Ethiopia 55 [106] Taxing and untaxing land: Current use assessment of farmland US 56 [107] Land tenure, fixed investment, and farm productivity Zambia…”
Section: Discussionmentioning
confidence: 99%
“…The main foreign studies on land use change in mountainous areas include rice farming efficiency in karst mountains [35], soil erosion response to land use change [36], effects of changes in paddy field use on soil bacterial communities in hilly and mountainous areas [37], the study of hydrological terraces in mountainous areas [38], the use of IBs and its effect on benthic fauna [39], the spatial assessment of forest cover and land use change [40], and impacts on landscape fragmentation on ecosystem services in mountain environments [41], etc. There is a relative paucity of research on land use in IBs.…”
Section: Introductionmentioning
confidence: 99%
“…In the Indonesian context, previous studies found the significant contribution of land use, fertilizer, labour, and climate [16], rainy [17] land size, income, and source of funding [18], farmer groups, agricultural counsellors [19], land rent, price of urea fertilizer, labour wage [20], training in relevant agricultural methods, the creation of wetlands, and an improvement in irrigation infrastructure [21] were among the important determinants of rice and paddy efficiency and productivity. Other studies found that age, formal education, participation of agricultural extension, and certified seeds [22], the level of effectiveness of standard operational procedure implementation [23] were also contributed to the increased rice productivity.…”
Section: Introductionmentioning
confidence: 99%